Applying a Visual Assessment Tool to Facial Linear Scars - Collins, Lindsey K.; Knackstedt, Thomas J.; Ganger, Pamela; Scherer, Emily; Samie, Faramarz H. (Facial Plastic Surgery, 2017)
Previous scar scales have focused on verbal descriptions. A nonverbal visual assessment tool would provide a simple way for patients and physicians to quantify scar appearance. The authors sought to use a validated visual assessment tool for linear surgical scars to assess linear scars on the face and to determine whether patients and surgeons rate scars similarly. A total of 143 patients with linear facial scars resulting from repair of Mohs micrographic surgery defects used the visual assessment tool to rate their surgical scar. Six physicians used the tool to rate a subset of the patients' scar photographs. The scar ratings for patients and physicians were compared. Among the scars rated by both the patients and physicians (n = 79), patients had a significantly lower mean (i.e., more favorable) rating compared with the physicians. This was a single-center study including only Caucasian patients. The visual assessment tool to rate linear surgical scars provided a simple method for both patients and physicians to assess the overall appearance of postsurgical scars. Difference in the scar ranking between patients and physicians indicate the importance of incorporating both patient and physician point of view when assessing scars.
Keywords: scar; scar scale; Mohs